Medication Adherence of Patient Assistance Program Recipients: A Pilot Study - Christian S. Conley, PharmD; Peter J. Hughes, PharmD, BCPS (University of Minnesota Libraries Publishing, 2012)
Purpose: Evaluate medication adherence of prescription assistance program recipients at an inner-city clinic.Methods: Surveys were administered at enrollment and 6 months following enrollment to patients who were either recipients of at least one patient assistance program (PAP) or had prescription benefits through Alabama Medicaid. Data on patient demographics, Morisky Medication Adherence Survey (MMAS) scores, mean possession ratio (MPR), and drug classes were collected for 6 months.Results: The baseline MMAS score concluded that both the PAP group and Alabama Medicaid group were highly motivated and highly knowledgeable regarding adherence to prescribed medications. After 6 months, administration of the same MMAS instrument resulted in a category change in the PAP group from highly motivated and knowledgeable to low motivation and high knowledge. The Medicaid MMAS adherence category did not change from baseline after 6 months. The 6-month mean MPR for the PAP and Medicaid groups were 0.542 and 0.823, respectively.Conclusion: Providing free or low-cost medication plus customary counseling should not be the sole interventions for the uninsured patient. In this study, PAP recipient MMAS score change and low mean MPR suggest that additional interventions are needed to ensure that PAP recipients adhere to prescribed therapies.